Application Of Modern Filling Materials In Pediatric Dentistry - Makhmudov Gulomjon Alisherovich; Ulmasov Azizjon Amindjanovich; Xolmuminov Nurali Nafasovich (Open Academia, 2025)
Pediatric dentistry has seen considerable improvements in materials and treatment options over the past few years. While other dental specialties have experienced tremendous developments in their materials and methods over the past forty years, pediatric dentistry has seemed to evolve much more slowly. Although we have enjoyed success with the treatments of the past, less invasive options involving fewer and more biocompatible chemicals can only benefit our patients and our practice of dentistry. What is good for our patients is good for our profession. This article will focus on the following new developments in pediatric dentistry: less invasive pulpal treatment, the switch from form cresol to MTA, bioactive restorations, and silver diamine fluoride
Keywords: considerable; profession; treatment; MTA